Does the kinorhynch have a hydrophobic body surface? Measurement of the wettability of a meiobenthic metazoan - Daisuke Ishii; Hiroshi Yamasaki; Ryosuke Uozumi; Euichi Hirose (Royal Society Open Science, 2016)
The body surface of aquatic invertebrates is generally thought to be hydrophilic to prevent the attachment of air bubbles. In contrast, some interstitial invertebrates, such as kinorhynchs and some crustaceans, have a hydrophobic body surface: they are often trapped at the water surface when the sediment in which they reside is mixed with air and water. Here, we directly measured the wettability of the body surface of the kinorhynch Echinoderes komatsui, using a microscopic contact angle meter. The intact body surface of live specimens was not hydrophobic, but the anterior part was less hydrophilic. Furthermore, washing with seawater significantly decreased the wettability of the body surface, but a hydrophilic surface was recovered after a 1 h incubation in seawater. We believe that the hydrophobic cuticle of the kinorhynch has a hydrophilic coat that is readily exfoliated by disturbance. Ultrastructural observations supported the presence of a mucus-like coating on the cuticle. Regulation of wettability is crucial to survival in shallow, fluctuating habitats for microscopic organisms and may also contribute to expansion of the dispersal range of these animals.